Postural steadiness and ankle force variability in peripheral neuropathy - Paxton, Roger J. (Motor Control, 2015)
INTRODUCTION: The purpose was to determine the effect of peripheral neuropathy (PN) on motor output variability for ankle muscles of older adults, and the relation between ankle motor variability and postural stability in PN patients. METHODS: Older adults with (O-PN) and without PN (O), and young adults (Y) underwent assessment of standing postural stability and ankle muscle force steadiness. RESULTS: O-PN displayed impaired ankle muscle force control and postural stability compared with O and Y groups. For O-PN, the amplitude of plantarflexor force fluctuations was moderately correlated with postural stability under no-vision conditions (r = 0.54, P = 0.01). DISCUSSION: The correlation of variations in ankle force with postural stability in PN suggests a contribution of ankle muscle dyscontrol to the postural instability that impacts physical function for older adults with PN.